Lithium Bond Chemistry in Lithium–Sulfur Batteries - Hou, Ting‐Zheng; Xu, Wen‐Tao; Chen, Xiang; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2017)
The lithium–sulfur (Li–S) battery is a promising high‐energy‐density storage system. The strong anchoring of intermediates is widely accepted to retard the shuttle of polysulfides in a working battery. However, the understanding of the intrinsic chemistry is still deficient. Inspired by the concept of hydrogen bond, herein we focus on the Li bond chemistry in Li–S batteries through sophisticated quantum chemical calculations, in combination with 7Li nuclear magnetic resonance (NMR) spectroscopy. Identified as Li bond, the strong dipole–dipole interaction between Li polysulfides and Li–S cathode materials originates from the electron‐rich donors (e.g., pyridinic nitrogen (pN)), and is enhanced by the inductive and conjugative effect of scaffold materials with π‐electrons (e.g., graphene). The chemical shift of Li polysulfides in 7Li NMR spectroscopy, being both theoretically predicted and experimentally verified, is suggested to serve as a quantitative descriptor of Li bond strength. These theoretical insights were further proved by actual electrochemical tests. This work highlights the importance of Li bond chemistry in Li–S cell and provides a deep comprehension, which is helpful to the cathode materials rational design and practical applications of Li–S batteries. Lithium bond chemistry in Li–S batteries is probed by sophisticated quantum chemical calculations in combination with 7Li NMR spectroscopy. The chemical shift in 7Li NMR spectroscopy is suggested to be a quantitative descriptor of Li bond strength, propelling the advances in Li–S chemistry through materials genome design and high throughput screening.